Potential of Telang Plant (Citoria ternatea) for Treatment of Aeromonas hydrophila Infection on Koi Fish (Cyprinus carpio) - Yuli Andriani; Asep Agus Handaka; Rosidah Rosidah; Rida Himyati (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
The aim of this study was to determine the effective concentration of telang leaf extract for the treatment of koi fish infected by the Aeromonas hydrophila bacteria and find out what clinical symptoms arise from Aeromonas hydrophila infection. The method used in this research was experimental using Completely Randomized Design (CRD) with five treatments and three replications. The treatment given was soaking koi fish infected with Aeromonas hydrophila in telang leaf extract for 48 hours with concentrations of 0, 150, 300, 450 and 600 ppm. Koi fish is infected with A. hydrophila by intramuscular injection of 0.1 ml/head with a bacterial density of 108 cfu/mL. The parameters observed were clinical symptoms including damage to fish body surface, fish response to feed and shock response. The data obtained were analyzed descriptively. The results showed that early clinical symptoms that arise are inflammation that is swelling and reddish color on the injection site and red spots. Other symptoms that occur are ulcers, hemorrhagic & inflammation, discoloration, exopthalmia and dropsy. The use of telang leaf extract with a concentration of 300 ppm was the best and effective treatment for treating the infected koi fish with A. hydrophila because within 9 days, the fish has recovered. It produced the fastest cure rate compared to other treatments.Keywords : Aeromonas hydrophila, koi fish, telang leaf extract, treatment, soaking